Leaving Work, Leaving Home: Job Loss and Socio-Geographic Mobility in Canada - Denier, Nicole (Canadian Public Policy, 2017)
The recent economic downturn magnified a routine occurrence in the Canadian labour market: job loss resulting from an employer downsizing, moving, or going out of business. Nevertheless, even in times of economic expansion, rates of involuntary job loss persist across a wide range of demographic and labour market groups. Moving is one way individuals may respond to job loss, relocating either to cheaper housing or in search of work. Drawing on data from the 1996–2010 Survey of Labour and Income Dynamics, this article examines the relationship between job loss and geographic mobility in Canada and provides evidence on the types of neighbourhoods to which individuals move. The findings establish job loss both as a key life course transition motivating residential mobility and long-distance migration in Canada and as a trigger event that initiates entry into high-deprivation areas.
https://www.researchgate.net/publication/313485728_Leaving_Work_Leaving_Home_Job_Loss_and_Socio-Geographic_Mobility_in_Canada